EDUTAINMENT AS A MODERN PEDAGOGICAL TECHNOLOGY IN CLASSROOM TEACHING PRACTICE FOR NON-PHILOLOGISTS - Yakubova Feruzakhon Askarovna; Musajanova Gulchehra Abdumanapovna (American Journals Publishing, 2024)
Language is the primary means of communication, without which it is difficult to imagine the existence and development of human society. In the contemporary world, undergoing significant changes in social relationships, communication tools (information technologies) require an increase in the communicative competence of students. This competence, developed through interaction with other communication participants, necessitates the exchange of ideas in various situations, proper language use, and adherence to conversational norms. In these conditions, the main goal of studying the Russian language is the formation of communicative abilities, i.e., the realization of interpersonal and intercultural communication in a non-native language. The article discusses the methodologies of implementing innovative technology - edutainment and modeling of gaming approaches.
Keywords: edutainment, methodology, humanization, approach, process, gaming modeling, gaming construction.